Experimental determination of hydrate phase equilibrium for different gas mixtures containing methane, carbon dioxide and nitrogen with motor current measurements - Sadeq, D.; Iglauer, Stefan; Lebedev, Maxim; Smith, C.; Barifcani, Ahmed (Elsevier Inc., 2017)
Hydrate dissociation equilibrium conditions for carbon dioxide + methane with water, nitrogen + methane with water and carbon dioxide + nitrogen with water were measured using cryogenic sapphire cell. Measurements were performed in the temperature range of 275.75 K–293.95 K and for pressures ranging from 5 MPa to 25 MPa. The resulting data indicate that as the carbon dioxide concentration is increased in the gas mixture, the gas hydrate equilibrium temperature increases. In contrast, by increasing the nitrogen concentration in the gas mixtures containing methane or carbon dioxide decreased the gas hydrate equilibrium temperatures. Furthermore, the cage occupancies for the carbon dioxide + methane system were evaluated using the Van der Waals and Platteeuw thermodynamic theory with the Langmuir adsorption model and Peng-Robinson equation of state. The data demonstrated the increasing promoting effect of carbon dioxide with its concentration. In addition, the motor current changes during the hydrate formation and dissociation processes were measured by keeping the rotation speed of the magnetic stirrer that was connected to a DC motor constant. The motor current measurements were reported and it showed that the hydrate plug formation and dissociation could be predicted by the changes in the motor current.